THE IDIOMS AND CULTURE-SPCIFIC ITEMS TRANSLATION STRATEGY FOR A CLASSIC NOVEL - Inayah Ahyana Rohmawati; Esti Junining; Pratnyawati Nuridi Suwarso (UIBU, 2022)
A translator must have a thorough grasp of a language and its culture in order to determine the most appropriate interpretation while being true to the culture's intent. They must understand the translation technique and category to maintain consistency while translating cultural texts such as idioms and culture-specific items. This study explored translation procedures for idioms and culture-specific items, as well as their categories, in light of these considerations. The researcher did a descriptive qualitative study utilizing two instruments from Lucy M. Montgomery's original novel